A Demonstration of Symbiotic Academic-Social Enterprise in Subsistence Marketplaces: Researching and Designing Customized Sustainability Literacy Education in Tanzania. Issue 2 (April 2021) - Viswanathan, Madhubalan; Baskentli, Sara; Gallage, Samanthika; Martin, Diane M.; Ramirez-Grigortsuk, Maria; Subrahmanyan, Saroja
This article demonstrates symbiotic academic-social enterprise (SASE), a bottom-up approach intertwined with the subsistence marketplace research stream. The SASE approach is unique in coevolving academic and social initiatives in parallel for the express purpose of achieving dual objectives: societally relevant research and social impact over an extended period. Distinct from typical action research approaches, the directionality between research and practice in this approach is circular or mutual rather than linear, the time frame continuous rather than discrete, and the unit of analysis the entire enterprise rather than a single project. Thus, SASE is fundamentally a bottom-up, learning-by-doing approach that developed in contexts characterized by a confluence of uncertainties for communities and a confluence of unfamiliarities for researchers and practitioners. The authors demonstrate this approach in the context of creating sustainability literacy education in Tanzania based on unique climate change impacts in the region. The academic research enterprise provides bottom-up insights about climate change and potential approaches to sustainability literacy education. A sustainability literacy education pilot project demonstrates an initiative in the social enterprise aspect of the approach. Finally, the authors derive public policy and marketing implications of SASE.